1988
DOI: 10.1093/brain/111.5.1211
|View full text |Cite
|
Sign up to set email alerts
|

Chorea and Myoclonus in the Monkey Induced by Gamma-Aminobutyric Acid Antagonism in the Lentiform Complex

Abstract: Experiments are described in which the gamma-aminobutyric acid (GABA) antagonist bicuculline was injected into the lentiform complex of conscious monkeys. Injections into either the lateral segment of the globus pallidus, or the medial part of the putamen, gave rise to chorea of the contralateral limbs and/or orofacial region. Control injections of vehicle alone were without effect. Injections of bicuculline into the lateral part of the putamen gave rise to contralateral myoclonus. The chorea produced by later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(81 citation statements)
references
References 0 publications
9
71
0
1
Order By: Relevance
“…The therapeutic efficacy of naloxone may be caused by the blockade of an increased transmission of endogenous opiates during dyskinesia. Similar to the effects of endomorphin-1, previous studies have shown that the local administration of the GABA receptor antagonist bicuculline in the globus pallidus stimulates dyskinesia (Crossman et al, 1988;Matsumura et al, 1995). In contrast, both local administration of the GABA agonist muscimol in the globus pallidus and chronic peripheral treatment with the opioid antagonist naloxone induced catalepsy in rats (Matsui and Kamioka, 1978;Egan et al, 1995).…”
Section: Functional Implicationsmentioning
confidence: 57%
“…The therapeutic efficacy of naloxone may be caused by the blockade of an increased transmission of endogenous opiates during dyskinesia. Similar to the effects of endomorphin-1, previous studies have shown that the local administration of the GABA receptor antagonist bicuculline in the globus pallidus stimulates dyskinesia (Crossman et al, 1988;Matsumura et al, 1995). In contrast, both local administration of the GABA agonist muscimol in the globus pallidus and chronic peripheral treatment with the opioid antagonist naloxone induced catalepsy in rats (Matsui and Kamioka, 1978;Egan et al, 1995).…”
Section: Functional Implicationsmentioning
confidence: 57%
“…Specifically, structural and functional imaging studies have found abnormalities in the striatum (Singer and Minzer, 2003), which is the main input structure of the basal ganglia (BG). The direct involvement of the striatum in tics is further supported by findings that disruption of striatal information transmission by localized application of a GABA A antagonist induces motor tics (Tarsy et al, 1978;Crossman et al, 1988;McCairn et al, 2009;Worbe et al, 2009).…”
Section: Introductionmentioning
confidence: 76%
“…In the present study, it was assumed that the mechanism by which the GABA A antagonist leads to recovery is one of disinhibition. Although there is no direct physiological evidence in this study to confirm that SC cells were disinhibited (i.e., depolarized), other studies using similar volumes and concentrations of bicuculline methiodide have demonstrated depolarization and have reported similar immediate postinjection effects (Chevalier et al, 1981;Hikosaka and Wurtz, 1985a;Buee et al, 1986;Crossman et al, 1988;Yoshida et al, 1991;Dean and Redgrave, 1992;Matsumura et al, 1995).…”
Section: The Recovery Mechanismmentioning
confidence: 56%